Population structure of the critically endangered Brazilian guitarfish Pseudobatos horkelii (Rhinobatidae) revealed by double-digest restriction site-associated DNA sequencing - Torres, Yan; Rotundo, Matheus Marcos; Vianna, Marcelo; Charvet, Patricia; Faria, Vicente Vieira; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Cruz, Vanessa Paes [UNESP] (Wiley, 2024)
Molecular analysis is a powerful tool for assessing and developing conservation strategies for endangered species. Elasmobranchs comprise one of the most threatened groups of vertebrates, with about one-third of the species subject to some degree of threat. This is the case for Pseudobatos horkelii, the Brazilian guitarfish, which has suffered severe population reductions (>80%) in recent decades, mainly through coastal overfishing. Understanding the genetic diversity of this species is paramount to applying adequate management and conservation strategies. In this context, the present study evaluated the genetic diversity of P. horkelii, employing single-nucleotide polymorphism (SNP) nuclear markers obtained by double-digest restriction site-associated DNA sequencing (ddRADseq). Samples collected in three areas along the Brazilian Coast (Rio de Janeiro, São Paulo, and Rio Grande do Sul) provided an average of 1,565,339 reads and 2,846 SNPs. The results indicate the presence of at least two genetically distinct populations along the Brazilian Coast, with molecular diversity differences noted among clusters. The heterozygosity excess observed in all populations is likely the result of a bottleneck, probably resulting from overfishing and habitat fragmentation. Moreover, the upwelling phenomenon in Cabo Frio, in the state of Rio de Janeiro, may have a significant influence over the observed genetic structure. The gene flow between the clusters was estimated and was noted as asymmetric between the populations studied. The observed patterns may be the result of the combination of biological characteristics and overfishing pressure in the past decades. The evidence of structured populations presenting genetic diversity differences provides insightful information for the development of stock management and conservation strategies for the Brazilian guitarfish.
Keywords: conservation; elasmobranchs; genetics; genomic; SNPs; threatened species